Challenges in Reforming Election Law in Indonesia - Basista, Ronny; Hidayat, Anto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This article explores the evolution of Indonesia's electoral system reforms since the restoration of democracy in 1998 and examines how these reforms have influenced Indonesian democracy through successive elections. To this end, the paper addresses two key inquiries: first, it identifies the primary stakeholders crucial for initiating and conducting the reform process; second, it outlines the objectives of these stakeholders in pursuing electoral reform. The findings suggest that the motivations of political elites are largely driven by a need to preserve and protect their own interests. This article aims to contribute to the discourse on electoral reform in Indonesia and its implications for the future trajectory of Indonesian democracy.